Evaluation of pregnancy outcomes in patients with a history of bariatric surgery - Ufuk Atlihan; Onur Yavuz; Can Ata; Huseyin Aytug Avsar; Selcuk Erkilinc (Frontiers in Medicine)
IntroductionObesity and overweight are significant risk factors for perinatal morbidity and mortality, and an increasing number of women of reproductive age are being offered bariatric surgery. The present study investigated the outcomes of pregnancies and births after bariatric surgery (BS).Materials and methodsAll patients who gave birth at our clinic between 2018 and 2023 were included in the study. Individuals who had undergone BS previously were identified using the hospital database, and their medical birth records were obtained for data on pregnancy, delivery, and perinatal results. The results of women who had undergone BS previously were analyzed by comparing them with other pregnancies.ResultsA total of 298 women who had undergone BS previously and 4,374 women who had not undergone surgeries were included in the study. The BS group had higher rates of abortion (p = 0.009) and IVF history (p < 0.001). Additionally, the incidence of pregnancy-induced hypertension (p < 0.001), preeclampsia (p = 0.04), gestational diabetes (GDM) (p < 0.001), premature birth (p < 0.001), cesarean delivery (p < 0.001), and small for gestational age (p < 0.001) was significantly higher in the BS group.ConclusionGiven the potential hazards associated with obesity in women of reproductive age, BS may be seen as a prudent course of therapy. Our study concluded that pregnancy prognosis is closely correlated with BMI at the time of pregnancy. Previous research revealed similar findings between groups in terms of pregnancy prognosis and pregnancy complications in obese and extremely obese patient groups.